Outcomes following the surgical management of left ventricular outflow tract obstruction; A systematic review and meta-analysis. (15th August 2018) - Collis, R.A.; Rahman, M.S.; Watkinson, O.; Guttmann, O.P.; O'Mahony, C.; Elliott, P.M.
Abstract: Background: Left ventricular outflow tract obstruction (LVOTO) causes exertional symptoms in two thirds of patients with hypertrophic cardiomyopathy (HCM). Consensus guidelines recommend surgical intervention in patients with drug refractory symptoms. The primary aim of this study was to perform a systematic review and meta-analysis to determine morbidity and mortality after surgery. Methods: Study Selection: Studies reporting outcomes following surgical intervention for symptomatic LVOTO in HCM. Data Extraction: Articles from searching two scientific databases (PubMed and Web of Science) were reviewed and data were extracted by two investigators. Meta-analysis of data was performed with heterogeneity assessed using I 2 statistic. Results: 85 studies were included in the systematic review and 35 studies in the meta-analysis. Contemporary early (<30 days) and late (>30 days) mortality following septal myectomy were 1.4% (CI 0.8, 2.4) I 2 9.0%, p = 0.36 and 0.7% (CI 0.3, 1.2) I 2 70.7%, p < 0.05 respectively. Sixty-eight studies (80%) reported perioperative complications. The contemporary rate of a perioperative ventricular septal defect was 1.4% (0.8, 2.3) I 2 0%, p < 0.05. Late morbidities including atrial fibrillation, stroke, heart failure and transplant were reported in fewer than 22% of studies and few studies compared mortality and clinical outcomes using different surgical approaches to LVOTO. The incidence rate (IR) of reintervention with a further surgical procedure was 0.3% (CI 0.2, 0.4) I 2 52.5%, p < 0.05. Conclusions: Contemporary surgical management of LVOTO is associated with low operative mortality rates but further studies are needed to investigate the impact of surgical therapy on non-fatal early and late complications. Highlights: Contemporary operative mortality following SM and SM with MV repair is low. Contemporary outcome data on the use of MV replacement for LVOTO is less robust. Reporting of long-term morbidity is less robust than that of early complications. Further studies are required on long-term surgical outcomes in LVOTO.